Automated Technology for Verification and Analysis : 13th International Symposium, ATVA 2015, Shanghai, China, October 12-15, 2015, Proceedings - Finkbeiner, Bernd; Pu, Geguang; Zhang, Lijun; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book constitutes the proceedings of the 13th International Symposium on Automated Technology for Verification and Analysis, ATVA 2015, held in Shanghai, China, in October 2015. The 27 revised papers presented together with 6 tool papers in this volume were carefully reviewed and selected from 95 submissions. They show current research on theoretical and practical aspects of automated analysis, verification and synthesis by providing an international forum for interaction among the researchers in academia and industry.
Keywords: Computer science; Logic design; Artificial intelligence; Programming Languages, Compilers, Interpreters; Logics and Meanings of Programs; Mathematical Logic and Formal Languages; Artificial Intelligence; Programming Techniques